KEDUDUKAN AHLI WARIS PEREMPUAN BALI DALAM PERSPEKTIF HUKUM WARIS DI INDONESIA - Putra Manu Harum, I Gede; Dharma Kusuma, A. A. Gede Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013)
This paper entitled “a female heir bali in perspective, indonesia “ the heir at law this paper uses the method research normative, with the approach of legislation. The aim of this research is to find out a female heir bali in perspective, legal heir because in bali who adheres to the system patrilinear or based on the line of descent purusha only provide rights mewaris to the house of a man or who made purusha. While the balinese women didn ' t have the right to the estate of a relic of his parents if the status is pradana. With kicked out decision number 01/KEP/PSM-3/MDP Bali/X/2010 by Majelis Utama Desa Pekraman (MUDP) on Pasamuhan Agung III on december 15 october 2010, and balinese women ( though the status is pradana ) is entitled to get an inheritance even though has men marrying and follows her husband.
Keywords: Heir, female, Hereditary Law